The Role Of Accounting Education In Promoting Entrepreneurship Sustainability In South Africa - Oladele Musili Folasade; Calvin Mahlaule; Nwosu Lilian Ifunanya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Re-examining the educational system is necessary, considering the startling number of South African graduates who are observed wandering the streets. The graduates must be equipped with skills that will enable them to support themselves independently. Since graduates have more opportunities for both paid and self-employment, accounting education is crucial. Students can use the abilities they have learned in their future family life and personal lives. It is necessary to acquire the fundamentals of accounting independently to maintain records of commercial activities. In this study, the importance of accounting education to sustainable enterprise was discussed. Accounting ideas such as "business as a going concern" and "business entity" were addressed, among others, as necessary for sustainable entrepreneurship. Issues that entrepreneurs face, such as inadequate funding, a lack of managerial expertise, and insufficient business planning, were discussed. It is evident that if South Africa’s education system effectively incorporated courses in accounting and entrepreneurship, graduates would be more inclined to create their own employment rather than seek jobs. Without such preparation, many graduates are left to fend for themselves when they are not offered employment after completing their studies. It is, therefore, recommended that the government provide funding to graduates with basic accounting skills and that thorough research be conducted before launching any commercial venture